HUBUNGAN USIA, TINGKAT PENDIDIKAN, DAN TINGKAT PENDAPATAN DENGAN KEPUASAN HIDUP PADA TIM PENGGERAK PEMBERDAYAAN KESEJAHTERAAN KELUARGA (TP-PKK) KALIGUNG BANYUWANGI: Correlation Between Age, Level Of Education, and Income Level With the Satisfaction Of Life at Family Welfare Empowerment Motivation Team Kaligung Banyuwangi - Erlin Qur'atul Aini; Septa Puspikawati (Journal of Community Mental Health and Public Policy, 2020)
Every individual has a standard of life satisfaction. The life satisfaction is also experienced by mothers who work and have income. Factors that affect life satisfaction are age, education, and income. This study aims to analyze the correlation of age, education level, and income level with the satisfaction of life at member of TP-PKK Kaligung Village, Blimbingsari District, Banyuwangi. This research was an analytical observational research with cross sectional design conducted on May 2019 in Kaligung Village, Blimbingsari District, Banyuwangi. Total samples of this study are 35 people from population of TP-PKK Kaligung Village, Blimbingsari District, Banyuwangi. Data were analyzed by Somer’s D Test. The result was satisfaction of life on members of TP-PKK Kaligung Village, Blimbingsari District, Banyuwangi on category very satisfied was 14%, satisfied was 54% and not satisfied was 2%. The majority of the age of respondents on late adult was 54%, education level respondents most elementary school was 37%, respondents have no income was 57%. The age variable (CI=95%; P = 0.45; r =-0.119) has no correlation with life satisfaction. The education level (CI=95%; P = 0.001; r = 0.365) and the income level (P = 0.036; r =-0.671) has significant correlation with life satisfaction. There was no correlation beetwen age and life satisfaction Then, if education levels was getting higher, life satisfaction would increased. Instead, if the income level was getting higher, the life satisfaction would decreased. Recommendation of this study, that each individual must view their life positively, be able to think rationally and objectively and be able to control theirself to stable in maintaining lifestyle when the level of education is not very high, and the level of income is getting higher so their life satisfaction does not decline.